Phytochemical Screening and Pharmacological Evaluation of Merremia vitifolia (Burm.f.) Hallier f. Leaf Extract (Chittagong University Journal of Biological Sciences, 2024)
The current investigation aimed to explore the various pharmacological properties of methanol extracts of Merremia vitifolia (Burm.f.) Hallier f. leaves (MEMV). Phytochemical analysis was performed following the established procedures. Using the hole board device, the anxiolytic action was measured. The oral glucose tolerance test (OGTT) was used to evaluate the hypoglycemic activity and the castor oil-induced diarrhea method was employed to explore the antidiarrheal activity in Swiss albino mice. Utilizing the brine shrimp lethality assay (BSLA), cytotoxicity was evaluated. In this study, it was observed that MEMV contained a number of active secondary metabolites such as triterpenes, alkaloids, glycosides, flavonoids, phenols and tannins. Compared to the control group, MEMV at 200 mg/kg and 400 mg/kg (p